Multiplane diffractive acoustic networks - Athanassiadis, Athanasios G.; Schlieder, Lennart; Melde, Kai; Volchkov, Valentin; Schölkopf, Bernhard; Fischer, Peer (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2023)
Acoustic holograms are able to control pressure fields with high spatial resolution, enabling complex fields to be projected with minimal hardware. This capability has made holograms attractive tools for applications, including manipulation, fabrication, cellular assembly, and ultrasound therapy. However, the performance benefits of acoustic holograms have traditionally come at the cost of temporal control. Once a hologram is fabricated, the field it produces is static and cannot be reconfigured. Here, we introduce a technique to project time-dynamic pressure fields by combining an input transducer array with a multiplane hologram, which is represented computationally as a diffractive acoustic network (DAN). By exciting different input elements in the array, we can project distinct and spatially complex amplitude fields to an output plane. We numerically show that the multiplane DAN outperforms a single-plane hologram, while using fewer total pixels. More generally, we show that adding more planes can increase the output quality of the DAN for a fixed number of degrees of freedom (DoFs; pixels). Finally, we leverage the pixel efficiency of the DAN to introduce a combinatorial projector that can project more output fields than there are transducer inputs. We experimentally demonstrate that a multiplane DAN could be used to realize such a projector.